2019
DOI: 10.1212/wnl.0000000000008243
|View full text |Cite
|
Sign up to set email alerts
|

Risk of natalizumab-associated PML in patients with MS is reduced with extended interval dosing

Abstract: Objective To use the large dataset from the Tysabri Outreach: Unified Commitment to Health (TOUCH) program to compare progressive multifocal leukoencephalopathy (PML) risk with natalizumab extended interval dosing (EID) vs standard interval dosing (SID) in patients with multiple sclerosis (MS). Methods This retrospective cohort study included anti-JC virus antibody-positive patients (n = 35,521) in the TOUCH database as of June 1, 2017. The effect of EID on PML risk was evaluated with 3 planned analyses using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 18 publications
2
118
0
7
Order By: Relevance
“…19 This has particularly been driven by the risk of progressive multifocal leukoencephalopathy (PML), a serious complication of natalizumab therapy in patients previously exposed to JC virus. 25 Retrospective studies of off-label treatment with EID have shown maintained efficacy 26,27 and reduced PML risk 28 compared with standard interval dosing. However, these studies are limited by possible selection bias due to nonrandomized design, and the efficacy and safety of EID is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…19 This has particularly been driven by the risk of progressive multifocal leukoencephalopathy (PML), a serious complication of natalizumab therapy in patients previously exposed to JC virus. 25 Retrospective studies of off-label treatment with EID have shown maintained efficacy 26,27 and reduced PML risk 28 compared with standard interval dosing. However, these studies are limited by possible selection bias due to nonrandomized design, and the efficacy and safety of EID is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell depletion frequently lasts much longer than the scheduled dosing interval, and extended-interval dosing should be considered, especially in patients who are B cell depleted (as measured by CD19/CD20 lymphocyte counts) at the time of the next scheduled dose or those with low levels of immunoglobulin G. Extended-interval dosing is already widely used in patients treated with natalizumab because of observational data showing a reduced risk of progressive multifocal leukoencephalopathy. 10 Whether this approach reduces the risk of other infections is unknown, but should be considered during the COVID-19 pandemic to reduce hospital visits.…”
Section: Disease-modifying Therapiesmentioning
confidence: 99%
“…Immunization with live but attenuated vaccines (MMR, VZV live vaccine, yellow fever), in contrast, should be completed at least 4 weeks prior to treatment initiation, Recently, the natalizumab product information has been updated [14], to include data suggestive of a lower risk of PML in patients treated with extended interval dosing (EID) [90]. However, it remains to be demonstrated that EID of natalizumab yields the same degree of efficacy if close clinical and MRI monitoring is performed [91].…”
Section: Vaccination Responsesmentioning
confidence: 99%